Le changement climatique et ses implications économiques sur le secteur touristique à la Guadeloupe et à la Martinique (Petites Antilles) - Louis Dupont (Études Caribéennes)
Climate change and the tourism sustainable development are important challenges for tourism future trends of many countries, including the French West Indies. Therefore, this study provides an evaluation of the likely economic effects of climate change on tourism sector in Guadeloupe and Martinique, and identifies four reasons why these countries should be concerned about the potential effects of climate change on tourism: (a) Guadeloupe and Martinique are island destinations very sensitive to climate change; (b) their intrinsic vulnerability and their infrastructure to sea level rise and extreme climatic events (e.g. hurricanes and floods); (c) the high dependence of their tourist industry on carbon-based fuels; and (d) up to date, no economic evaluation of climate change on tourism sector in Guadeloupe and Martinique is provided. Therefore, this study attempted to quantify the likely effects of the changes in the climatic factors on the economy of the French West Indies. There are four main objectives in this study. The first is to examine the factors that influence the demand and supply tourism in Guadeloupe and Martinique. The second is to forecast the impact of climate change to tourism arrivals until 2050 under two scenarios from the intergovernmental panel on climate change (IPCC) – A2: pessimistic scenario and B2: optimistic scenario-. Third is to evaluate and forecast the cost of climate change to the tourism sector until 2100. The fourth is to recommend to authorities the adaptation and mitigation strategies that can be undertaken by the tourism sector to French West Indies to address climate change.Following Harvey (1990), a Basic Structural Model (BSM) and a General structural Model (GSM), are employed to model tourist arrivals to Martinique. A tourism climatic index (TCI) conceptualized by Mieczkowski (1985) is used in this model to capture the elements of climate that impact on a destination’s experience. The results suggest that under both scenarios, the island’s key tourism climatic features will probably decline, and therefore, negatively impact on the destination experience of visitors. Tourism losses due to climate change are projected in 2100 to 45 millions euros in Guadeloupe, or 0.7% of its GDP, and to 60 millions euros in Martinique, or 0,8% of its GDP.